Power Optimization of UOWC-MIMO-OFDM System Based on PSO-WF Algorithm - Bai, JR; Li, N; Nie, J; Liang, XY (Journal of physics. Conference series, 2023)
Under the constraint that the total transmission power is constant, when multiple input multiple output orthogonal frequency division multiplexing (MIMO-OFDM) technology is applied to the signal transmission design in the underwater optical wireless communication system (UOWC), the traditional water-filling algorithm (WF) uses mathematical derivation to solve the optimization problem, which requires multiple Lagrangian optimization solutions. In order to reduce the computational complexity and accelerate the convergence speed, a particle swarm optimization (PSO-WF) algorithm for water injection is proposed. It randomly selects particles in the target area, calculates the fitness, and gradually approximates the optimal solution to avoid negative power distribution. The simulation results show that, compared with the average power allocation scheme, the algorithm improves the system capacity and operation efficiency by about 80%; Compared with WF algorithm, it greatly reduces the complexity.